MACROECONOMIC DOWNTURNS AND PRICE SENSITIVITY IN VOCATIONAL EDTECH: IMPLICATIONS FOR BUSINESS STRATEGY IN SCHOTERS BY RUANGGURU WORK ABROAD PROGRAM - Najla Rasikha Putri Harza; Harimukti Wandebori (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research examines the Schoters by Ruangguru Work Abroad Program, focusing on strategies to sustain growth and profitability amid rising price sensitivity and macroeconomic uncertainty in Indonesia. As inflation, wage stagnation, and shifting youth aspirations reshape consumer behavior, vocational EdTech providers must adapt through innovative pricing and strategic positioning. A mixed-method approach was employed. Quantitatively, the study utilized the Price Sensitivity Meter and Conjoint Analysis to measure willingness to pay and attribute trade-offs. Qualitatively, user interviews provided deeper insights into motivations, barriers, and psychographic segmentation. From these findings, corporate-, business-, and functional-level strategies were developed based on macroeconomic and consumer dynamics. Strategic recommendations were then formulated using established business strategy frameworks and theories. This study contributes by bridging strategic management theory with macroeconomic trends and psychographic segmentation in an emerging market context. It also offers actionable insights for EdTech firms navigating uncertainty while pursuing sustainable growth.